Carboxyl ester lipase hybrid 1 (CEL-HYB1) haplotypes confer varying risk for chronic pancreatitis - Gergő Berke; Máté Sándor; Xunjun K. Xiao; Mark E. Lowe; Maren Ewers; Bálint Erőss; Emmanuelle Masson; Balázs Csaba Németh; Áron Vincze; László Czakó; Agnieszka Magdalena Rygiel; Jonas Rosendahl; et al. (Scientific Reports)
Abstract The CEL-HYB1 hybrid allele of the carboxyl ester lipase (CEL) gene and its pseudogene (CELP) has been associated with chronic pancreatitis (CP). Recent work indicated that amino acid positions 488 and 548 in CEL-HYB1 determined pathogenicity. Haplotype Thr488-Ile548 was associated with CP while haplotypes Thr488-Thr548 and Ile488-Thr548 were benign. However, functional analysis revealed that Thr488 is the primary determinant of CEL-HYB1 misfolding and associated endoplasmic reticulum (ER) stress. To address this contradiction, we analyzed a cohort from Hungary and found significantly increased CEL-HYB1 carrier frequency in CP cases (9/319, 2.8%) versus controls (5/618, 0.8%), yielding an odds ratio of 3.6 (95% confidence interval 1.2–10.7, P = 0.024). All CEL-HYB1 positive carriers from Hungary had the Thr488-Thr548 haplotype. We analyzed the haplotype distribution of reported CEL-HYB1 carriers from three European cohorts and found that 14/29 CP cases from Germany and 2/6 CP cases from Poland carried the Thr488-Ile548 haplotype, which was absent in CEL-HYB1 positive controls from Germany (n = 13) and Poland (n = 8). All patients (n = 17) and controls (n = 9) from France carrying CEL-HYB1 contained the Thr488-Thr548 haplotype. Functional studies using transfected cells indicated that both CEL-HYB1 haplotypes induced significant ER stress and the Thr488-Ile548 haplotype had a stronger effect. We conclude that the Thr488-Thr548 haplotype of CEL-HYB1 is widespread in Europe and increases CP risk by almost fourfold. In contrast, the Thr488-Ile548 haplotype is regionally restricted, but confers markedly stronger CP risk.